Estimation of Carbon Stock Loss from Land Use Changes in Bogor Regency PENDUGAAN HILANGNYA CADANGAN KARBON DARI PERUBAHAN PENGGUNAAN LAHAN DI KABUPATEN BOGOR - Gatot Setiawana; Lailan Syaufina; Nining Puspaningsih (Jurnal Silvikultur Tropika, 2016)
One of the primary sectors that contribute on national greenhouse gas emissions are land use changes. Land use change contributes approximately 50% of national emissions. In the context of climate change, land use change can contribute as the source and sink of carbon. Bogor Regency is one of the districts close to the capital city of Indonesia and industrial areas so that the intensity of land use changes are very dynamic. The aim of this study was to determine the dynamics of land use change and CO2-eq emissions from year 2000 to 2014 in Bogor Regency. Approach to estimate carbon stock change in this study was conducted with stock difference method, the method of calculation of carbon which assesses the carbon deposits at two time points. Most of land use change occurred in mixed garden, wetland, open land, and shrubs that converted into settlement that amounted to 33 283 ha or approximately 11.12% of the Bogor Regency, while the rate of total annual emissions of the greatest historical, namely in the period 2005-2009 amounted to 681 006.94 tones of CO2-eq / year. Increase of emissions occurred in the conversion into other land uses that have a lower carbon stock.Key words: land use change, greenhouse gas emissions, carbon stock